The Use of Quizizz as Learning Media in English Language Learning to Enhance Student Motivation and Interest - Fadilah, Farah (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This research aims to explore the use of the learning media Quizizz in learning English as an effort to increase students' motivation and interest in learning at SMKN 5 Makassar. This research aimed to analyze the impact of using Quizizz on students' motivation and interest in learning and identify the strengths and weaknesses of using the media. The research method used was classroom action research involving English class students at SMKN 5 Makassar. The research was conducted in several cycles, where each cycle consisted of planning, action, observation, and reflection. Data were collected through observation, interviews, and questionnaires which were analyzed qualitatively. The results of this research indicate that the use of Quizizz learning media positively impacts students' motivation and interest in learning. students show a higher level of activity during learning with Quizizz, as they engage in interactive quizzes and get immediate feedback. In addition, students also show a higher interest in learning English through this media. This research implies that the use of Quizizz learning media can be applied in the context of learning English at SMKN 5 Makassar and other schools to increase learning effectiveness and strengthen students' interest in learning. Keywords: Quizizz, English, Motivation, Interest in Learning